2019
DOI: 10.1002/adem.201900613
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorous Catalytic‐Doping of Silicon Alloys for the Use in Silicon Heterojunction Solar Cells

Abstract: Herein, the effectiveness of post-deposition catalytic-doping (cat-doping) on various doped silicon alloys, i.e., microcrystalline silicon (μc-Si:H), nanocrystalline silicon oxide (nc-SiOx:H), and microcrystalline silicon carbide (μc-SiC:H), for the use in silicon heterojunction solar cells is investigated. Phosphorous (P) profiles by secondary ion mass spectrometry (SIMS) reveal the P distribution and its difference in these three silicon alloy films. Conductivity and effective charge carrier lifetime of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As discussed in our former work, the coexistence of thermal annealing, hydrogenation, and P doping effects during the Cat-doping process leads to the improvement in the passivation quality. Both the thermal annealing effect and hydrogenation effect during the process help to saturate the dangling bonds and therefore improve the passivation in the stack .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…As discussed in our former work, the coexistence of thermal annealing, hydrogenation, and P doping effects during the Cat-doping process leads to the improvement in the passivation quality. Both the thermal annealing effect and hydrogenation effect during the process help to saturate the dangling bonds and therefore improve the passivation in the stack .…”
Section: Discussionmentioning
confidence: 74%
“…Former studies and this work have shown that Cat-doping on μc-Si:H and a-Si:H usually has larger N P and a larger penetration depth than that in c-Si. 25,27 It has also been found that the N P from Cat-doping is larger in c-Si with the (100) orientation than that in the (111) orientation, 35 where actually, thermal diffusion is also easier in the (100) than (111) wafers. 36 These studies give hints that the diffusion of P into silicon films during low T sub Cat-doping might depend largely on the defective microstructures of different silicon films.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 3c–e, the lower lifetime of the PECVD precursors compared to the reference is due to lack of field effect passivation. As discussed in our previous work, [ 40 ] the coexistence of thermal annealing and phosphorus doping in the Cat‐doping process could lead to an improvement in chemical passivation and field effect passivation, respectively. Since the thickness of the a‐Si:H(i) layer used in the passivation structure is thinner than the penetration depth of the P atoms, a shallow doped region should form on the surface of the c‐Si substrate, which could also act as a front surface field and improve the passivation.…”
Section: Cat‐doping On Shj Solar Cellsmentioning
confidence: 99%